Analysis of the mechanism of gas bubble break-up in liquids during the self-aspirating impeller operation - Stelmach Jacek; Kuncewicz Czesław; Musoski Radosław (Chemical and Process Engineering)
Feasibility of a model of gas bubble break-up and coalescence in an air-lift column enabling determination of bubble size distributions in a mixer with a self-aspirating impeller has been attempted in this paper. According to velocity measurements made by the PIV method with a self-aspirating impeller and Smagorinski’s model, the spatial distribution of turbulent energy dissipation rate close to the impeller was determined. This allowed to positively verify the dependence of gas bubble velocity used in the model, in relation to turbulent energy dissipation rate. Furthermore, the range of the eddy sizes capable of breaking up the gas bubbles was determined. The verified model was found to be greatly useful, but because of the simplifying assumptions some discrepancies of experimental and model results were observed.